Clinical impact of prophylactic antibiotics in kidney transplantation: A retrospective observational cohort study with historical comparison - Sang Ah Lee; Jin-Myung Kim; Hye Eun Kwon; Youngmin Ko; Joo Hee Jung; Sung Shin; Young Hoon Kim; Sung-Han Kim; Hyunwook Kwon (PLoS ONE, 2025)
Purpose Optimal perioperative antibiotic prophylaxis in kidney transplantation remains undefined despite routine antibiotic administration to prevent infections. In this retrospective observational cohort study with historical comparison, we compared the clinical efficacy of 6 days of ampicillin/sulbactam vs. a single dose of cefazolin. Materials and methods We retrospectively analyzed 2322 kidney transplantation recipients at a single center, with the evaluation period spanning from 2015 through 2021. Patients were divided into 2 groups based on the perioperative antibiotic regimen received: 971 patients received ampicillin/sulbactam, and 1351 received cefazolin. This study focused on evaluating the impact of these regimens on postoperative infection incidence and the 6-month acute rejection (AR) rates. Results The cefazolin group exhibited a tendency toward higher urinary tract infection rates within 1 month after transplantation (3.4% vs. 2.2%, p= = 0.078). There were no significant differences in surgical site infections between the groups. The 6-month AR rates were significantly lower in the cefazolin group than in the ampicillin/sulbactam group (5.1% vs. 7.9%, p= = 0.009). Cefazolin was also confirmed to be significantly associated with reduced 6-month AR rates in the multivariable logistic regression analysis (odds ratio 0.63, 95% confidence interval [0.45-0.89], p= = 0.009). Conclusion In this study, we observed that a single dose of cefazolin as perioperative antibiotic prophylaxis may lead to higher rates of postoperative urinary tract infections, but it could potentially lower the incidence of acute rejection within six months.